Pelatihan Akuntansi Keuangan Kampung Pada Guru-Guru Akuntansi Kota dan Kabupaten Jayapura - Bill J.C. Pangayow; Sylvia Christina Daat (UNIVERSITAS CENDERAWASIH, 2018)
The Village Government or in the Papua Province called Kampung is the smallest government that can manage its finances independently. As a financial manager, the village government must account for the finances managed by preparing financial statements. Village fund managers are usually entrusted to senior high school or vocational high school accounting departments who have studied accounting at their school. High school or vocational teachers as providers of cognitive knowledge related to village financial accounting are very important to know and be skilled in financial management in the village so they can share their knowledge with their students in high school or vocational. Therefore, village finance training is very necessary for accounting teachers in Jayapura City and Regency. This activity was successfully implemented and achieved its objectives because it was implemented with practical training methods. The tutorial is done in front of the class and immediately followed by participants. In the last two sessions there were practices for village accounting exercises so that participants could take part in activities and achieve goals well.